Quality assessments in multiplexing - Shah, Asadullah; Bhatti, Zeeshan (IIUM Press, 2011)
Considering low bit rate sources the quality of speech suffers mainly by a factor, such as quantization noise. Multiplexing efficiency is therefore, based upon the encoding sources bit rates. Lower the coding rates, better the efficiency but on the expense of quality. The quality in multiplexing is assessed by two means, objectively and subjectively. In this chapter the quality assessment by both objective and subjective means is discussed for the STDM design considerations